Cover Image, Volume 117, Number 3, March 1, 2018. Issue 3 (15th March 2018) - Stevenson, Marc G.; Musters, Annelie H.; Geertzen, Jan H.B.; van Leeuwen, Barbara L.; Hoekstra, Harald J.; Been, Lukas B.
Abstract : The cover image, by Marc G. Stevenson et al., is based on the Research Article Amputations for extremity soft tissue sarcoma in an era of limb salvage treatment: Local control and survival, DOI10.1002/jso.24881 .